Help wanted : must love books - Sumner Johnson, Janet (Capstone Editions, a Capstone imprint, 2020)
"Shailey loves bedtime until her father gets distracted by a new job, so she advertises for a replacement "Bedtime Storyteller" and finds herself interviewing her favorite fairytale characters." --